Relationship Between Leaving Children at Home Alone and Their Mental Health: Results From the A-CHILD Study in Japan - Doi, Satomi; Fujiwara, Takeo; Isumi, Aya; Ochi, Manami; Kato, Tsuguhiko (Frontiers in Psychiatry, 2018)
Leaving children at home alone is considered a form of “neglect” in most developed countries. In Japan, this practice is not prohibited, probably because this country is considered to have relatively safe communities for children. The impact of leaving children at home alone on their mental health is a controversial issue, and few studies have examined it to date. The aim of this study was to examine the impact of leaving children aged 6 or 7 years at home alone on their mental health, focusing on both the positive and negative aspects; that is, resilience, difficult behavior, and prosocial behavior. Data from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study were used. The caregivers of all children in the first grade in Adachi City, Tokyo, were targeted, of whom 80% completed the questionnaire (N = 4,291). Among the analytical sample which comprises those who completed both exposure and outcome variables (N = 4,195), 2,190 (52.2%) children had never been left at home alone, 1,581 (37.7%) children were left at home alone less than once a week, and 424 (10.1%) children were left at home alone once a week or more. Child resilience was measured using the Children’s Resilient Coping Scale, and difficult behavior (emotional symptoms, conduct problems, hyperactivity/inattention, and peer relationship problems) and prosocial behavior using the Strength and Difficulty Questionnaire. Multivariate regression analyses were performed to examine the dose-response association between leaving children at home alone and child mental health, followed by propensity-score matching as a pseudo-randomized controlled trial to reduce potential confounding. The results showed that leaving children at home alone once a week or more, but not less than once a week, was associated with total difficulties scores, especially conduct problems, hyperactive/inattention, and peer relationship problems. These findings indicate that leaving children at home alone should be avoided in Japan, as is recommended in North America.